Risk Behavior and Psychological Stress on the Incidence of Hypertension among Productive Age in Urban Communities - Prahassiwi, Alifia Apriliani; Sukendra, Dyah Mahendrasari (GoAcademica Research & Publishing, 2024)
Indonesia has an increasing trend of hypertension cases annually. The incidence of hypertension in Indonesia was 25,8% in 2013 and 34,1% in 2018, with a higher prevalence in urban areas. Although the prevalence of hypertension is higher in older age, the potential burden of disease is greater at a younger age in experiencing cardiovascular disease and kidney failure in the future. This study aims to determine the relationship between risk behavior and psychological stress on hypertension among productive age in urban Indonesia. This is analytical observational research with a cross-sectional design that uses secondary data from the fifth Indonesian Family Life Survey (IFLS-5). The sample size was 3193 respondents who met the inclusion and exclusion criteria. The analysis is univariate, bivariate, and multivariate. Bivariate analysis using Chi-square and Fisher test obtained factors related to hypertension incidence are age 55-64 years old (p<0,001), age 45-54 years old (p<0,001), age 35-44 years old (p<0,001), education level (p=0,004), physical activity (p=0,020), and obesity (p<0,001). There is no significant relationship in other variables, including psychological stress. While through the test of logistic regression in multivariate analysis, factors that affect hypertension are age (p<0,001), gender (p=0,011), and obesity (p<0,001). The study concludes that obesity is the strongest influential variable on the incidence of hypertension among productive age in urban Indonesia. After controlling for other variables, obese individuals had 3,538 times more potential to develop hypertension compared to non-obese individuals (OR=3,538; 95% CI=2,763-4,532).